Objectively measured physical activity patterns, sedentary time and parent-reported screen-time across the day in four-year-old Swedish children - Daniel Berglind; Per Tynelius (BMC, 2017)
Abstract Background Physical activity (PA) improves health outcomes accumulating evidence suggests that sedentary time (ST), especially parent-reported screen-time, is associated with negative health outcomes in children. The aim of the present study is to describe levels and patterns of PA and ST across the day and week and activity pattern differences between the sexes, across all weekdays and time spent in and outside the preschool in four-year old children. Methods In total 899 four-year old Swedish children who had both complete questionnaire data on screen-time behaviors and objective activity variables and at least 4 days, including one weekend day, with more than 10 h of GT3X+ Actigraph accelerometer wear time data were included in the study. Patterns of PA and ST across the day and week and differences between sexes, weekdays vs. weekend days and time in preschool vs. time spent outside preschool were assessed. Results Children engaged in 150 min (SD 73) and 102 min (SD 60) of screen-time on weekend days and weekdays, with 97% and 86% of children exceeding the 1 h guideline for screen-time on weekend days and weekdays, respectively. Accelerometer data showed that boys are more active and less sedentary compared with girls and both sexes were more active and less sedentary on weekdays compared with weekend days, while parent-reported data showed that boys engage in more screen-time compared with girls. Children accumulated 24.8 min (SD. 19) MVPA during preschool time and 26.6 min (SD. 16) outside preschool hours on weekdays, compared with 22.4 min (SD. 18) MVPA during preschool time and 25.3 min (SD. 22) outside preschool hours on weekend days. Conclusions Four-year old Swedish children display different activity patterns across the day on weekdays compared to weekend days, with preschool hours during weekdays being the most active segments and preschool hours during weekend days being the least active segments of the day.